Analisis Hukum Pengadaan Barang/Jasa Terhadap Kasus Korupsi Proyek Tol Mbz: Pelanggaran Tender dan Pertanggungjawaban Korporasi - Setiawan, Antonius Ryan Dandy; Syah, Aurellia Zerikha; Sihotang, Josua Ferdinand; Narindra, Rochella Amalia (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes legal violations in the procurement of goods/services in the corruption case of the Sheikh Mohammed bin Zayed (MBZ) Toll Road project, focusing on deviations from the principles of Presidential Regulation Number 16 of 2018 and the application of corporate criminal liability under Article 20 of Law Number 31 of 1999 as amended by Law Number 20 of 2001 on the Eradication of Corruption Crimes (UU Tipikor). The case reveals patterns of tender collusion, technical specification manipulation, budget mark-ups, and collusion causing state losses up to IDR 510 billion, violating principles of efficiency, transparency, accountability, competitiveness, and value for money. Using a normative juridical approach with secondary data from regulations, court decisions, and scholarly literature, the analysis concludes that corporations like KSO Waskita-Acset meet the corporate fault criteria under Supreme Court Regulation Number 13 of 2016, warranting fines, additional sanctions such as blacklisting, and asset recovery. The study emphasizes the need for procurement system reforms to prevent systemic corruption.